Reducing the mother-to-child transmission of HIV: findings from an early infant diagnosis program in Delta state Nigeria - Ibobo, Judith A.; Nwose, Ezekiel Uba; Chime, Helen (International Journal Of Community Medicine And Public Health, 2017)
Background: Mother-to-child transmission (MTCT) of HIV has been a global issue being addressed with prevention of mother to child transmission (PMTCT) strategy. Nigeria is said to be responsible for 30% of the global burden of MTCT of HIV. Hence, Delta state of Nigeria had implemented its own PMTCT in line with the global plan to eliminate MTCT. This paper evaluates the determinants and level of effectives of PMTCT with a view to develop a framework to review the program in Delta state. Methods: This was a narrative literature review which aimed at appraising available reports on PMTCT services and related data. In particular, the ‘Delta state development performance: health sector report 1991–2013’ was appraised. Results: Generally, Delta state has improved on infant survival better than national baseline. Specifically, on PMTCT, more women (average 2.9%) than men (average 2.1%) have tested positive for HIV in the 5 years period of 2008–2012 free screening. Further, the report indicates that the State has achieved 78% of eligible facilities offering PMTCT services in the state, but only 23% coverage of pregnancies. Conclusions: In the context of cost effectiveness as well as improvement in service delivery, there is a need to investigate the success rates of health facilities that are offering PMTCT services. There is also need to investigate the barriers to PMTCT that may be prevailing in Delta state.